2018
DOI: 10.3390/ijms19092763
|View full text |Cite
|
Sign up to set email alerts
|

2-Bromo-4′-methoxychalcone and 2-Iodo-4′-methoxychalcone Prevent Progression of Hyperglycemia and Obesity via 5′-Adenosine-Monophosphate-Activated Protein Kinase in Diet-Induced Obese Mice

Abstract: Obesity and diabetes are global health-threatening issues. Interestingly, the mechanism of these pathologies is quite different among individuals. The discovery and development of new categories of medicines from diverse sources are urgently needed for preventing and treating diabetes and other metabolic disorders. Previously, we reported that chalcones are important for preventing biological disorders, such as diabetes. In this study, we demonstrate that the synthetic halogen-containing chalcone derivatives 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…As an AMPK activator, DMC could be useful to prevent the progression of hyperglycemia, and thus it may serve as a lead compound for a new class of drugs active against obesity and type 2 diabetes. Similar effects have been reported with structurally close chalcone derivatives such as 2-bromo- and 2-iodo-4′-methoxychalcones [ 47 ].…”
Section: Other Pharmacological Effects: Diabetes Preventionsupporting
confidence: 82%
See 1 more Smart Citation
“…As an AMPK activator, DMC could be useful to prevent the progression of hyperglycemia, and thus it may serve as a lead compound for a new class of drugs active against obesity and type 2 diabetes. Similar effects have been reported with structurally close chalcone derivatives such as 2-bromo- and 2-iodo-4′-methoxychalcones [ 47 ].…”
Section: Other Pharmacological Effects: Diabetes Preventionsupporting
confidence: 82%
“…For example, the chalcone phloretin exhibits anticancer effects via AMPK activation [ 64 ]. Other anticancer and/or anti-inflammatory chalcone derivatives have been shown to activate AMPK, such as isoliquiritigenin [ 65 ], 2-bromo-4′-methoxychalcone [ 47 ], the prenylated chalcone xanthohumol [ 66 ], the kava chalcone flavokawain B [ 67 ] and other chalcones [ [68] , [69] , [70] ]. An interesting case is that of licochalcone A which displays antitumor and anti-inflammatory properties, like DMC [ 71 ].…”
Section: Molecular Targets Of Dmcmentioning
confidence: 99%
“…Several studies have demonstrated that, either from natural sources or synthetic, chalcones can impact on glucose and lipid metabolism and their health benefits have been studied in relation to type 2 diabetes [ 379 ]. Chalcones have shown hypoglycemic capacity, the ability to modulate food intake and activate AMPK, as well as antioxidant, anti-inflammatory, anticancer, anti-obesity, hepatoprotective and neuroprotective properties [ 380 , 381 , 382 , 383 , 384 , 385 , 386 , 387 , 388 , 389 , 390 , 391 , 392 ] Although there are no many studies in humans the effects of chalcones in the obese phenotype in animal models are similar to the ones described for other flavonoids, thus suggesting a potential therapeutic role of these group of bioactive compounds.…”
Section: Chalconesmentioning
confidence: 99%
“…They are open-chain flavonoid compounds that possess a basic skeleton of A, B rings linked with α, β-unsaturated carbonyl system [14,15]. Different plant-derived types of chalcones have been isolated containing a variety of substituted elements, including methyl, methoxy and hydroxy substituents on both of the aromatic rings [16]. The most advantageous and attractive factor in producing chalcones and their derivatives are that they can be reacted via a one-step protocol using an aldol condensation between a benzaldehyde and an acetophenone in the presence of a base.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a chalcone derivative with iodo substitution at position 2 on A-ring, which never occurred in natural resources and named 2-iodo-4′-methoxychalcone (CHA79, Figure 1), has been shown to be more potent than other anti-diabetic drugs. It is noteworthy that halogen-containing chalcone derivatives are very rare in the plant kingdom, but can easily be scaled up synthetically as mentioned above [15,16]. CHA79 is suggested to act as a 5′-adenosine-monophosphate-activated protein kinase (AMPK) activator and possesses anti-diabetic activity in the literature [16].…”
Section: Introductionmentioning
confidence: 99%